Worker-specific effects of globalisation - Hartmut Egger; Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper sets up a general equilibrium model, in which firms are heterogeneous due to productivity differences and workers have fairness preferences and hence provide full effort only if their factor return is sufficiently high. With the wage considered to be fair by workers depending on the operating profits of the firm in which they are employed, more productive firms in this setting are not only larger and make higher profits but they also have to pay higher wages due to rent-sharing. This mechanism leads to wage differentiation even if all workers share the same individual characteristics. We use this framework to study worker-specific effects of trade between two symmetric countries. Exporters in this setting make higher operating profits and hence have to pay higher wages than non-exporters. This exporter wage premium provides a source for losses from trade and, all other things equal, makes a negative employment effect of trade more likely. Furthermore, it contributes significantly to a general increase in intra-group income inequality among production workers when a country moves from autarky to trade.
Keywords: F12; F15; F16; 330; heterogeneous firms; wage inequality; fair wages; involuntary unemployment; Lohnstruktur; Unfreiwillige Arbeitslosigkeit; Lohnbildung; Gerechtigkeit; Außenhandelswirtschaft; Globalisierung; Beschäftigungseffekt; Theorie